Photochemistry : Vol. 38 - Albini, Angelo (Cambridge : Royal Society of Chemistry, The LaVergne : Ingram Publisher Services [Distributor], 2010)
Annotation The breadth of scientific and technological interests in the general topic of photochemistry is truly enormous and includes for example,such diverse areas as microelectronics, atmospheric chemistry, organic synthesis, non-conventional photoimaging, photosynthesis, solar energy conversion, polymer technologies, and spectroscopy. Photochemistry reviews photo-induced processes that have relevance to the above wide-ranging academic and commercial disciplines, and interests in chemistry, physics, biology and technology. In order to provide easy access to this vast and varied literature, Photochemistry comprises sections sub-divided by chromophore and reaction type, and also a comprehensive section on polymer photochemistry.Throughout, emphasis is placed on useful applications of photochemistry.
Includes Index.